Cholesterol esters form supercooled lipid droplets whose nucleation is facilitated by triacylglycerols - Calvin Dumesnil; Lauri Vanharanta; Xavier Prasanna; Mohyeddine Omrane; Maxime Carpentier; Apoorva Bhapkar; Giray Enkavi; Veijo T. Salo; Ilpo Vattulainen; Elina Ikonen; Abdou Rachid Thiam (Nature Communications, 2023)
Dumesnil et al. report that cholesterol esters (CE), which only melt above body temperature, form supercooled liquid crystalline lipid droplets (LD). Triacylglycerols (TG) solubilize CE to help CE LD nucleation. Through clustering TGs in the ER membrane, seipin controls CE LD nucleation sites.